REMINERALIZATION PRODUCTS EFFECT ON HUMAN ENAMEL IN VITRO STUDY - SILAGHI DUMITRESCU, Laura; MIHĂILESCU, Ana Maria; MUNTEAN, Alexandrina; SAROSI, Liana-Codruța; PRODAN, Doina; SIMU, Meda Romana; MOLDOVAN, Marioara; KUI, Andrea; PĂSTRĂV, Mihaela (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The aim of this in vitro study was to assess the remineralization process of human enamel, using two commercial pastes (containing calcium, phosphates, hydroxyl-apatite and sodium fluoride) and an experimental gel (obtained from fruit extract). 40 caries free extracted human teeth were divided into 4 groups: 3 study groups (n=12), and 1 control group (n=4). For the study groups, the remineralization agent differed: GC Tooth Mousse, Recaldent, Remin Pro (Voco) and an experimental gel made by “Raluca Ripan” Chemistry Institute (Cluj Napoca, Romania). ATR-FTIR (Jasco-610, Japan) was employed to verify the protective effect of the remineralizing products on enamel. UV-Vis spectra were used to determine mineral loss and gain during demineralization-remineralization process. No significant statistic difference emerged between specimens in study groups and the specimens in control group. Under the limitations of the in vitro study, the application of the tested product proved to be effective on enamel remineralization.